Hypoalbuminaemia and Postoperative Outcomes in Inflammatory Bowel Disease: the NSQIP Surgical Cohort. (23rd April 2019) - Nguyen, Geoffrey C; Du, Lillian; Chong, Rachel Y; Jackson, Timothy D
Abstract: Background: The inflammatory bowel diseases [IBD], including Crohn's disease [CD] and ulcerative colitis [UC], frequently lead to bowel surgery. Hypoalbuminaemia has been shown to be a prognostic factor for outcomes following surgery for other indications, and we sought to determine its role in predicting IBD-related postoperative outcomes. Methods: We included patients who underwent IBD-related major abdominal surgery in the American College of Surgeons' National Surgical Quality Improvement Program [ACS-NSQIP] between 2005 and 2012. We assessed the impact of indicators of protein-energy malnutrition [PEM] including hypoalbuminaemia, weight loss, and body mass index on postoperative outcomes. Results: We identified 10 913 IBD patients [6082 Crohn's disease and 4831 ulcerative colitis] who underwent bowel surgery. The prevalence of modest and severe hypoalbuminaemia was 17% and 24%, respectively; 30-day mortality was higher in Crohn's patients with modest and severe hypoalbuminaemia compared with those with normal albumin levels preoperatively [0.7% vs 0.2%, p < 0.05; 2.4% vs 0.2%, p < 0.01]. The same was true for patients with UC with modest and severe hypoalbuminaemia [0.9% vs 0.1%, p < 0.01; 5.6% vs 0.1%, p < 0.01]. Overall infectious complications were more common in the presence of severe hypoalbuminaemia for CD [20% vs 13%, p < 0.01]. and UC [28% vs 15%, p < 0.01] patients. Last, there were higher rates of extra-intestinal, non-septic complications in both CD and UC patients with hypoalbuminaemia compared with those with normal albumin levels. Conclusions: This study suggests that moderate-severe hypoalbuminaemia is associated with worse IBD-related postoperative outcomes and may have a role in preoperative risk stratification.